The Art Model as Performer - Aurélie Debaene (Aesthetic Investigations, 2021)
In this paper, I argue that modelling occupies a curious role in the art making process, and that it constitutes a hybrid art form. Modelling is intriguingly under-research in aesthetics, despite it being a cornerstone of art education and deeply involved in various art practices. It functions both within a supportive role to further the goals of art making, while also retaining the creative agency and performance of the professional model upon which the artist, photographer, or wider crew rely. This ability entails not merely helping to steer a posing session, but experimenting with and adapting to any unexpected issues that arise in the course of the session. To understand the salient performative qualities of modelling, I first focus on expert movement, improvisation, and style. Second, I reflect on how modelling corresponds to creativity and skill. Finally, I propose that the model is a performer, and that, ultimately, modelling should be recognised as a hybrid collaborative art form which incorporates qualities of various performing arts.